2013
DOI: 10.2753/ree1540-496x490104
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate Controller Ownership and Firm Value in Taiwan

Abstract: Using a panel of 242 Taiwanese listed firms during a ten-year period (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006), this study tests whether there is an optimal ratio of ownership ultimate control that maximizes firm value. This work adopts Tobin's q as the proxy for firm value and finds that cash flow rights less than 27.8 percent and control rights between 32.34 percent and 34.03 percent are an optimal level of ownership ultimate control to maximize firm value. This distribution of financing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…It is evident from various Asian countries that ownership divergence and firm's profitability are in nonlinear relationship with each other (Lin and Lin, 2013;Wiwattanakantang, 2001;Utama et al, 2017). The study of Hanafi et al (2018) also shows significant relationship between ownership and firm performance, especially the saturated ownership increases the performance.…”
Section: Overview Of Sugar Industrymentioning
confidence: 92%
“…It is evident from various Asian countries that ownership divergence and firm's profitability are in nonlinear relationship with each other (Lin and Lin, 2013;Wiwattanakantang, 2001;Utama et al, 2017). The study of Hanafi et al (2018) also shows significant relationship between ownership and firm performance, especially the saturated ownership increases the performance.…”
Section: Overview Of Sugar Industrymentioning
confidence: 92%
“…Our paper contributes to the existing literature by presenting more recent evidence of the impact of ownerships structure on firms' performance, and the dynamics of markets that make the effect changes with time. We also contribute to the existing literature by providing complementary evidence on the effect of governance and ownerships structure on firms' performance in the Asian context (Wiwattanakantang, 2001;Lin and Lin, 2013;Utama et al, 2017). To the best of our knowledge, there has been no study on emerging markets that compares the effect of ownerships structure on performance using the setting of different financial crises.…”
Section: Introductionmentioning
confidence: 92%
“…The evidence from country-specific studies, especially in the Asian context, can be found in Wiwattanakantang (2001) for Thailand, Lin and Lin (2013) for Taiwan and Utama et al (2017) for Indonesia. Wiwattanakantang (2001) and Lin and Lin (2013) report a non-linear effect of ownership on firms' performance.…”
Section: Corporate Governance Ownership Structure and Firm Performancementioning
confidence: 99%
“…Obszerną grupę badań stanowią analizy dotyczące wpływu struktury akcjonariatu na efektywność funkcjonowania spółek (Thomsen, Pedersen 2000;Varcholova, Beslerova 2013;Zatora, Maryniak 2013) 6 . Wyniki prowadzonych badań dowodzą, iż struktura akcjonariatu jest również determinantą struktury źródeł finansowania (Wilczyński 2015), wartości przedsiębiorstwa (Lin, Lin 2013), ryzyka upadłości (Poletti-Hughes, Ozkan 2014), płynności akcji i stopnia asymetrii informacji (Attig i in. 2006).…”
Section: Przegląd Badań Empirycznych Nad Strukturą Akcjonariatuunclassified